2019
DOI: 10.1126/science.aax0379
|View full text |Cite
|
Sign up to set email alerts
|

A rice gene that confers broad-spectrum resistance to β-triketone herbicides

Abstract: The genetic variation of rice cultivars provides a resource for further varietal improvement through breeding. Some rice varieties are sensitive to benzobicyclon (BBC), a β-triketone herbicide that inhibits 4-hydroxyphenylpyruvate dioxygenase (HPPD). Here we identify a rice gene, HIS1 (HPPD INHIBITOR SENSITIVE 1), that confers resistance to BBC and other β-triketone herbicides. We show that HIS1 encodes an Fe(II)/2-oxoglutarate–dependent oxygenase that detoxifies β-triketone herbicides by catalyzing their hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
92
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 32 publications
(19 reference statements)
6
92
0
Order By: Relevance
“…These P450 inhibitor studies suggest that multiple metabolic genes/enzymes (including P450s) may be involved in weed resistance to HPPD‐inhibiting herbicides. A recent study has identified that a gene encoding an Fe(II)/2‐oxoglutarate‐dependent oxygenase endows resistance to HPPD‐inhibiting herbicides in rice . However, genes conferring metabolic resistance to HPPD‐inhibiting herbicides have not been identified in weeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These P450 inhibitor studies suggest that multiple metabolic genes/enzymes (including P450s) may be involved in weed resistance to HPPD‐inhibiting herbicides. A recent study has identified that a gene encoding an Fe(II)/2‐oxoglutarate‐dependent oxygenase endows resistance to HPPD‐inhibiting herbicides in rice . However, genes conferring metabolic resistance to HPPD‐inhibiting herbicides have not been identified in weeds.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has identified that a gene encoding an Fe(II)/2-oxoglutarate-dependent oxygenase endows resistance to HPPD-inhibiting herbicides in rice. 37 However, genes conferring metabolic resistance to HPPD-inhibiting herbicides have not been identified in weeds.…”
Section: Discussionmentioning
confidence: 99%
“…Benzobicyclon (BBC) is a novel paddy-bleaching β-triketone herbicide (bTH) (Komatsubara et al, 2009). It can be applied from pre-emergence to early post-emergence in paddy elds, showing broad-spectrum resistance against annual grasses, sedges, and broadleaf weeds but being harmless to TPR and DSR (Bi et al, 2018;Komatsubara et al, 2009;Maeda et al, 2019). bTHs mainly target 4-hydroxyphenylpyruvate dioxygenase (HPPD), which is a key step in the biosynthesis of plastoquinone and tocopherol (Kraehmer et al, 2014;Moran, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As an herbicide that inhibits HPPD, BBC is different from herbicides that inhibit acetolactate synthetase (ALS) and acetyl-CoA carboxylase (ACCase), which are widely used in paddy elds (Jabusch and Tjeerdema, 2005;Kumar and Ladha, 2011;Mahajan et al, 2013), so it can be used as a rotation herbicide in these elds. The number of weed species with resistance to herbicides that inhibit HPPD is minimal (Gould et al, 2018), and BBC shows e cacy against paddy weeds resistant to other types of herbicide, including sulfonylureas (Maeda et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation